Pengembangan E-Comic Berkarakter Islami Guna Meningkatkan Literasi Matematis - Aura Diva Azzahra; Fina Tri Wahyuni (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: This study aims to develop an Islamic-character mathematical e-comic and assess its validity, practicality, and effectiveness in improving students’ mathematical literacy. The method used was Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were 7th-grade students of MTs NU Darul Anwar. The results showed that the media was developed systematically based on ADDIE stages. Expert validation scored an average of 89% (very valid), and practicality tests on small and large groups reached 84% and 82%, respectively (very practical). Effectiveness testing showed an improvement in students’ mathematical literacy with a gain score of 0.46 (moderate category). The media is considered feasible and has the potential to improve students’ mathematical literacy in the topic of social arithmetic.Abstrak: Penelitian ini bertujuan mengembangkan media e-comic matematika berkarakter Islami serta menguji validitas, kepraktisan, dan efektivitasnya dalam meningkatkan literasi matematis siswa. Metode yang digunakan adalah Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subjek penelitian adalah siswa kelas VII MTs NU Darul Anwar. Hasil menunjukkan media dikembangkan secara sistematis sesuai tahapan ADDIE. Validasi ahli memperoleh skor rata-rata 89% (sangat valid), dan uji kepraktisan kelompok kecil dan besar masing-masing 84% dan 82% (sangat praktis). Pengujian efektivitas menunjukkan peningkatan literasi matematis siswa dengan nilai gain sebesar 0,46 (kategori sedang). Media dinilai layak dan berpotensi meningkatkan literasi matematis siswa pada materi aritmetika sosial.